The osteoinductive potential of different root-end filling materials in a rat femur model - Seçkin Aksu; Ebru Delikan; Ayşe Özcan Küçük; Zehra Demiray Asoğlu; Şakir Necat Yılmaz (Scientific Reports, 2024)
Abstract In pediatric dentistry, the enduring success of root-end filling materials employed for the establishment of apical plugs in immature teeth undergoing endodontic intervention is contingent upon their possessing a robust osteoinductive capacity. Hence, the primary objective of this study was to histologically assess the osteoinductive potential of four distinct dental materials, specifically recommended for retrograde filling applications, utilizing an animal hard tissue model. Within the designed experimental model, two bone defects measuring 2 mm in diameter and 2 mm in depth were created in both femurs of a cohort comprising 21 male Wistar albino rats. The first defect in the right femur was left blank as the control group, and Neo MTA Plus was placed in the second defect. The EndoSequence BCRRM Fast Set Putty was placed in the first of the defects on the left femur, and Endo Repair was placed in the second defect. Subjects were sacrificed after 7, 14, and 28 days of follow-up, and sections were examined to assess the degree of inflammation, connective tissue formation, and new bone formation. The data were statistically evaluated with Kruskal‒Wallis and post hoc Dunn's tests using SPSS 12 software. The bone healing levels of the Neo MTA Plus group were significantly higher than those of the other groups in all periods (p < 0.05). Bone organization in all groups decreased over time, and fibrous tissue was enriched. The results of this study demonstrate that NeoMta Plus has superior osteoinductive properties compared to other materials but that EndoSequence and Endo Repair have the potential to be developed.